STRATEGIES AND APPROACHES TO IMPLEMENTING RELIGIOUS MODERATION AT THE STATE HINDU COLLEGE (STAHN) JAWA DWIPA KLATEN, CENTRAL JAVA - Eko Pujianto; Nur Khoiri; Nurkolis (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to analyze the strategies and approaches used in implementing religious moderation at Sekolah Tinggi Agama Hindu Negeri (STAHN) Jawa Dwipa Klaten, Central Java. Using a qualitative descriptive design, data were collected through in-depth interviews, observations, and documentation involving students, lecturers, and institutional leaders. The findings indicate that the implementation of religious moderation is carried out through integrative, participatory, and contextual approaches. The integrative approach is reflected in the alignment of religious moderation values within the curriculum and academic activities, while the participatory approach is visible through student involvement in social programs, cultural activities, and community service. Additionally, the contextual approach adapts strategies to local wisdom and campus cultural dynamics. The study concludes that leadership commitment, collaborative academic culture, and supportive institutional policies play a vital role in strengthening tolerance, inclusiveness, and national identity. STAHN Jawa Dwipa Klaten can serve as a model for religious moderation implementation in higher education institutions.